The assessment of food security among floods victims at Bera, Pahang / Salehmatul Akma Mohamad Salleh - Mohamad Salleh, Salehmatul Akma (2016)
Food security is defined as physical and economic access by all people at all times with adequate basic food, safe and nutritious foods to meet nutritional needs and fund for an active and healthy life. In Malaysia, since 1971 flooding was occurred and the average rainfall is approximately 2,500mm a year and make it the one of the countries that have the heaviest rainfall in the world which it can lead to occurring flood disaster. This study is a qualitative study which was conducted on people that was affected with flood at the location in Bera, Pahang, Malaysia‘ The main objective of 1he study was to understand the respondents’ needs for food security during flood disaster. While, the specific objective was to determine a nutritional slams of flood Victims, assess on the impact of flood on crop production and livestock and lastly to assess the four dimension in food security among flood Victims. These research was assess by using a combination of key informant meetings, personal interviews and anthropometrics measurements. Total respondents are 10 individuals from different village was selected for interview. The range of age of the respondents were from 28 years old to 63 years old. All the answer from the respondent was recorded by using voice recorder. The overall results from interviewing session with 10 respondent were most of them had said that they needs food supply and clean water supply for food security during flood disaster. In term of food, they does not have any problems due to the food aid that they had receive during flood disaster which is too enough for them but the main problems comes from inadequate supplying of clean water due 10 crowded people at the relocation center. As a conclusion, food and clean water supply are very important needs for food security during flood disaster. Thus, government and non-government organization have to cogitate on the strategies to improvise the needs for food security during flood disaster especially on water supply.